On ID-Hamiltonian [a, b]-factor - Zhou, Sizhong; Wu, Jie; Pan, Quanru (Utilitas Mathematica, 2019)
Let a, b be two integers with 2 < a < b. An (a, b]-factor F of a graph G is called a Hamiltonian [a,b]-factor if F includes a Hamiltonian cycle. We say that G has an ID-Hamiltonian [a,b]-factor if after deleting any independent set of G the remaining graph of G includes a Hamiltonian [a, b]-factor. In this paper, we obtain two sufficient conditions for graphs to have ID-Hamiltonian [a, b]-factors. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.